2000
DOI: 10.1212/wnl.54.7.1453
|View full text |Cite
|
Sign up to set email alerts
|

Cross-reactive antibodies against GM2 and CMV-infected fibroblasts in Guillain–Barré syndrome

Abstract: CMV-infected fibroblasts express gangliosidelike epitopes that recognize specifically anti-GM2 antibodies. These results support the hypothesis that antiganglioside antibodies in CMV-infected GBS patients are induced by molecular mimicry between GM2 and antigens that are induced by a CMV infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
39
0
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(43 citation statements)
references
References 32 publications
2
39
0
2
Order By: Relevance
“…Viral agents are hypothesized to lead to anti-ganglioside response via presentation of host ganglioside during viral budding from infected cells (Evans and Webb, 1986;Ang et al, 2000). The characteristics and pathological properties of our anti-GD1a antibodies and antisera arising in response to GD1a-KLH immunization were very similar to those seen in response to LOS immunization.…”
Section: Discussionmentioning
confidence: 56%
“…Viral agents are hypothesized to lead to anti-ganglioside response via presentation of host ganglioside during viral budding from infected cells (Evans and Webb, 1986;Ang et al, 2000). The characteristics and pathological properties of our anti-GD1a antibodies and antisera arising in response to GD1a-KLH immunization were very similar to those seen in response to LOS immunization.…”
Section: Discussionmentioning
confidence: 56%
“…The implication of antiganglioside GM2 antibodies in the pathogenesis of GBS related to CMV has been described [15] . It has been demonstrated that CMV-infected fibroblasts express ganglioside-like epitopes that specifically recognize anti-GM2 antibodies [16] . These results suggest that, in CMVinfected GBS patients, infected cells with CMV can express epitopes inducing an immune response against gangliosides.…”
Section: Discussionmentioning
confidence: 99%
“…The preceding infections with CMV, EBV, and Campylobacter jejuni in patients with the syndrome have been reported to be associated with severe axonal degeneration and presence of anti-ganglioside antibodies [Hughes et al, 1999;Hadden et al, 2001;Yuki, 2001]. Generation of anti-ganglioside antibodies has been attributed to molecular mimicry between the epitopes of the infecting pathogen and/or epitopes expressed by infected cells [Shimoya et al, 1997;Ang et al, 2000]. In the present case there was no recent infection with CMV, EBV and also of the clinical features of Campylobacter enteritis.…”
Section: Discussionmentioning
confidence: 99%